2016
DOI: 10.1177/107327481602300109
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Perceptions of Anal Cancer Screening and Behaviors among Gay and Bisexual Men Infected with HIV

Abstract: Background The incidence of anal cancer is on the rise among HIV-infected men who have sex with men (MSM). Given the increasing availability of screening, this study explored anal cancer screening awareness and behaviors among MSM infected with HIV. Methods In-depth interviews were conducted with 58 MSM infected with HIV. Results Other than 2 participants treated for anal cancer and 3 treated for precancerous anal lesions, the majority of participants had never heard of anal cancer. Men reported lack of aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
(18 reference statements)
2
17
0
Order By: Relevance
“…The findings also indicated the crucial role of consultations with GP in increasing participants' understanding of abnormal results, leading to a more realistic and lower cancer risk perception and moderating anxiety. This is consistent with previous results showing that primary care physicians have been reported to be the main sources of sexual health check‐up for GBM, that HIV/primary care specialists have a central role in raising awareness about the need to screen for anal cancer among HIV‐positive GBM and that physicians' recommendations are the main facilitator to screening for anal dysplasia . Further studies need to investigate whether patients with a recent connection with their healthcare providers also benefit from consultations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings also indicated the crucial role of consultations with GP in increasing participants' understanding of abnormal results, leading to a more realistic and lower cancer risk perception and moderating anxiety. This is consistent with previous results showing that primary care physicians have been reported to be the main sources of sexual health check‐up for GBM, that HIV/primary care specialists have a central role in raising awareness about the need to screen for anal cancer among HIV‐positive GBM and that physicians' recommendations are the main facilitator to screening for anal dysplasia . Further studies need to investigate whether patients with a recent connection with their healthcare providers also benefit from consultations.…”
Section: Discussionsupporting
confidence: 91%
“…Recent works showed that GBM are largely unaware of the link between HPV and anal cancer, with HIV‐negative men having lower awareness . Lack of knowledge and recommendations from doctors are the greatest barriers to screening for HIV‐positive men …”
Section: Introductionmentioning
confidence: 99%
“…In this sample, more than half of the participants had previously been screened for anal dysplasia via anal Pap smear, a higher rate than what was previously reported in another study with English-speaking populations. 33 Foreign-born Latino HIV-infected GBM noted that health-care provider recommendation alone was the driving factor for anal Pap smear completion. Therefore, it is critical that HIV primary care providers offer culturally sensitive anal dysplasia screening information for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Staff from the community-based organizations posted fliers at their organizations. The fliers provided information about the topic of interest (cancer prevention), inclusion criteria (HIV-infected, self-identify as a gay or bisexual man, 18 years of age or older, fluent in Spanish [a previous study was conducted in English], 33 and resides in Miami-Dade County), and a Google number that rang directly to the bilingual research assistant’s cellphone. After potential participants called the study number, the bilingual research assistant screened them for eligibility and asked them to recommend a date, time, and location for the interview.…”
Section: Methodsmentioning
confidence: 99%
“…This may be partially attributed to lack of communication regarding anal cancer symptoms from physician to patient during the screening visit or higher levels of pain and discomfort, but there may also be a poor understanding of anal cancer risk in general among MSM. Prior studies of MSM in the United States and Australia have shown that the majority of participants were unaware of anal cancer and its associated risks and qualitatively suggested a perception that HPV-associated cancers only affected women and caused cervical cancer [27,28]. Knowledge and awareness of HPV as a risk factor for anal cancer may be even more scarce in sub-Saharan Africa where it is rarely reported in cancer registries [29].…”
Section: Discussionmentioning
confidence: 99%